Carotenoid-derived bioactive metabolites shape plant root architecture to adapt to the rhizospheric environments - Ke, Danping; Guo, Jinggong; Li, Kun; Wang, Yujie; Han, Xiaomeng; Fu, Weiwei; Miao, Yuchen; Jia, Kun-Peng (Frontiers in Plant Science, 2022)
Roots are important plant organs for the uptake of water and nutrient elements. Plant root development is finely regulated by endogenous signals and environmental cues, which shapes the root system architecture to optimize the plant growth and adapt to the rhizospheric environments. Carotenoids are precursors of plant hormones strigolactones (SLs) and ABA, as well as multiple bioactive molecules. Numerous studies have demonstrated SLs and ABA as essential regulators of plant root growth and development. In addition, a lot carotenoid-derived bioactive metabolites are recently identified as plant root growth regulators, such as anchorene, ꞵ-cyclocitral, retinal and zaxinone. However, our knowledge on how these metabolites affect the root architecture to cope with various stressors and how they interact with each other during these processes is still quite limited. In the present review, we will briefly introduce the biosynthesis of carotenoid-derived root regulators and elaborate their biological functions on root development and architecture, focusing on their contribution to the rhizospheric environmental adaption of plants